2007
DOI: 10.1159/000111161
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Ultrasound Techniques Applied to Body Fat Measurement

Abstract: Aims: To evaluate the accuracy of body fat percentage (BF%) estimates from a portable, non-traumatizing ultrasound device with high accuracy and reliability compared to dual-energy X-ray absorptiometry (DEXA), the reference technique. Design: Cross-validation between ultrasound technique (UT), DEXA, air displacement plethysmography (ADP) and bioelectrical impedance (BIA) was developed in the study. Subjects: A total of 89 healthy subjects (41 women, 48 men), aged 48.4 ± 17.7 (mean ± SD), with Body mass index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 38 publications
3
34
1
Order By: Relevance
“…That result allows us to state that CT is more appropriate than is ultrasound for the study of abdominal fat in the characterization of individual body composition, given that it shows a greater correlation with the various anthropometric parameters evaluated, as evidenced by the Pearson’s correlation coefficients of 0.82, 0.77, 0.79, and 0.84, respectively, for BMI, waist circumference, hip circumference, and abdominal circumference. This leads us to agree with several authors who consider CT the reference for the evaluation of body fat (8,11-15,19-21) . However, it is necessary to consider the risks of the use of ionizing radiation for an evaluation whose clinical significance is relative; that is, although CT provides greater reproducibility and correlates better with the anthropometric data, its use does not seem justifiable in view of the individual risk-benefit ratio (22) .…”
Section: Discussionsupporting
confidence: 92%
“…That result allows us to state that CT is more appropriate than is ultrasound for the study of abdominal fat in the characterization of individual body composition, given that it shows a greater correlation with the various anthropometric parameters evaluated, as evidenced by the Pearson’s correlation coefficients of 0.82, 0.77, 0.79, and 0.84, respectively, for BMI, waist circumference, hip circumference, and abdominal circumference. This leads us to agree with several authors who consider CT the reference for the evaluation of body fat (8,11-15,19-21) . However, it is necessary to consider the risks of the use of ionizing radiation for an evaluation whose clinical significance is relative; that is, although CT provides greater reproducibility and correlates better with the anthropometric data, its use does not seem justifiable in view of the individual risk-benefit ratio (22) .…”
Section: Discussionsupporting
confidence: 92%
“…Recently Pineau et al has validated both US skinfold and BIS measurements in adults against dual-energy X-ray absorptiometry. In that study US has shown very good accuracy, while BIS has shown less accuracy than US but better than air displacement plethysmography (12). BIS predictions of %FM in infants improve with age compared with simple anthropometric measurements (4) and could benefit pediatric populations if more equations developed for infants after 5 mo of age.…”
Section: Volume 81 | Number 3 | March 2017mentioning
confidence: 86%
“…The SCTT (skin thickness and the skin-fat interface to fat-muscle interface distance that were easily defined on the scan) was measured directly from images on the screen using electronic calipers (12) (Figure 1). All of the measurements were performed by one experienced sonographer (DG) with previously reported high intraobserver reliability (9).…”
Section: Reference Matches Def Def All But H All But H Abc Abmentioning
confidence: 99%
“…The higher the ultrasound frequency the greater the resolution, but there is a decrease in penetration. There is not yet any standardized protocol for using ultrasound to measure subcutaneous fat, but the majority of the studies included in this review have used a 5 MHz, B-mode transducer; however, a relatively new portable ultrasound device (BodyMetrix, BX2000, IntelaMetrix, Inc., Livermore, CA) designed and marketed specifically for body composition assessment uses a 2.5 MHz, A-mode transducer, and Pineau and colleagues [18, 19] validated body fat measurements against DXA using an A-mode transducer with a 2.25 MHz frequency.…”
Section: Technical Principlesmentioning
confidence: 99%